Franchising Occulture: On the Introduction and Developments of Occult Reality TV in Sweden - Moberg, Jessica (Nordic journal of religion and society, 2019)
Occult reality is a stream in reality TV, and part of a transnational franchise industry where adaptations of program concepts are being made in new contexts. This article scrutinizes the introduction and developments of occult reality in Sweden. The article answers the following questions: How are Swedish series framed by program concepts from the international TV market? What are the similarities between the narratives and aesthetics in occult reality and that of other TV genres? Which role do genre conventions and program concepts play in shaping contemporary spiritualities and their representations? The main material consists of Swedish versions of occult reality shows. Analytical inspiration is drawn from theories of mediatization and media logic. The article shows a native "occult reality universe" was constructed around The Unknown (Det okända) where mediums cast out spirits from people's homes. Like several programs in the reality genre, The Unknown creates the events it documents. The Unknown script taps into other scripts from trends both in reality TV and horror fiction, and participants have been given roles and tasks on the basis of those scripts. For mediums, participation in fact implied taking up "house cleansings" as an adaption to the script and franchise.